A framework for designing mathematics instruction using comics at the primary school level - Chu, Yun Li Lynnette; Toh, Tin Lam (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2020)
Developing primary school students’ interest in and getting them motivated to learn mathematics has been a perennial focus of educators. The use of comics for classroom instruction is an area gaining more attention from educators. In this paper, we review some existing education literature on the impact of comics on students’ cognitive and affective learning needs. We also propose a TSCT (Theme, Storyline, Character, Text) framework for educators to design instructional material using comics for mathematics instruction in the primary mathematics classroom. With the TSCT framework, we demonstrate the design of one comics mathematics lesson on the topic of Fraction.